2008
DOI: 10.1002/j.2168-9830.2008.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Thinking about Static Equilibrium: Insights from Written Explanations to a Concept Question

Abstract: Students' thinking during an assessment task was monitored by analyzing their explanations of answers to a multiple‐choice question about the equilibrium of bodies under given loads. Based on coding by independent raters, we found that nearly all students explained answers by appealing to force and/or moment summation; they differed principally on whether they applied both force and moment equilibrium and did so consistently. Correlations between answer selection and explanation as found from coding suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…This confusion is also strengthened by the use of those words in everyday life with a meaning that does not coincide with their scientific meaning. Several studies have shown that students encounter difficulties in understanding simple familiar or academic static equilibrium cases from mechanics (Gunstone and White 1981;Palmer 2001;Ortiz, Heron, and Shaffer 2005;Newcomer and Steif 2008;Flores-García et al 2010) and some others show that the understanding of equilibrium and stability is strongly disturbed in case of moving reference frames (Tamayo, Canu, and Duque 2012;Canu, de Hosson, and Duque 2014) even if students know the discipline's criteria and formulae.…”
Section: Introductionmentioning
confidence: 97%
“…This confusion is also strengthened by the use of those words in everyday life with a meaning that does not coincide with their scientific meaning. Several studies have shown that students encounter difficulties in understanding simple familiar or academic static equilibrium cases from mechanics (Gunstone and White 1981;Palmer 2001;Ortiz, Heron, and Shaffer 2005;Newcomer and Steif 2008;Flores-García et al 2010) and some others show that the understanding of equilibrium and stability is strongly disturbed in case of moving reference frames (Tamayo, Canu, and Duque 2012;Canu, de Hosson, and Duque 2014) even if students know the discipline's criteria and formulae.…”
Section: Introductionmentioning
confidence: 97%
“…It was necessary for the concepts involved in the coding scheme to change depending on the content for each problem and the phenomena involved. The major categories for coding student responses for each concept are similar to that used in a related work from the physics/statics literature 15 :…”
Section: Methodsmentioning
confidence: 99%
“…It was necessary for the concepts involved in the coding scheme to change depending on the content for each problem and the phenomena involved. The major categories for coding student responses for each concept are similar to that used in a related work from physics/statics literature 15 :…”
Section: Methodsmentioning
confidence: 99%